Impact of slum upgrading to river water quality in Yogyakarta city, Indonesia - Endar Rohmadi; Masahiko Sekine; Bakti Setiawan (Jurnal Teknosains, 2022)
Due to a lack of proper sanitation services, the disposal of residential wastewater from slum areas has become one of the river pollution contributors. In Yogyakarta slums were concentrated along the riverbanks of the Winongo, Code and Gajahwong rivers. Due to slum upgrading, slums have declined from 264.5 ha to 114.72 ha between 2016 and 2020. This research aims to determine the correlation between slum upgrading and river water quality. The data was acquired from the Government of Yogyakarta City, Indonesia, and examined using ten water parameters from 2013 to 2021. Using Pearson Correlation Coefficient and Spearman Rank, it was found that population density positively correlated with Total Coliform and Fecal Coliform (p<0.05). It was also seen that the slum ratio showed a positive correlation with BOD, COD, TSS, pH, and NH3-N (p<0.05). The number of WWTP had a positive correlation with PO4-P (p= 0.037), whereas the number of connected houses to WWTP reported a positive correlation with P04-P (p=0.028). In addition, a significant decrease in BOD, COD, NH3-N, pH, and TSS were found using the Paired t-test and the Wilcoxon Signed-Rank test. (p<0.05). Slum upgrading notably reduced organic pollutants and suspended solids. However, the performance of WWTP did not perform a maximal contribution to reducing PO4-P and Coliform; therefore, it is necessary to improve the performance. This study might be used to enhance the river and urban management in Yogyakarta City.